Efektivitas Penggunaan Model Latihan Kebugaran “Bbc Exercise” Untuk Pemeliharaan Kebugaran Jasmani Mahasiswa - Bile, Robertus Lili; Suharharjana, Suharharjana (UNIVERSITAS NEGERI MAKASSSAR, 2019)
ABSTRACTThe problem of physical fitness is still a global pandemic which is increasingly widespread in many circles of society. Singentari lifestyle is one of the factors causing health problems such as degenerative diseases, decreased physical fitness, injury prone, decreased cognitive function and so on. Students with a relatively high level of activity tend to ignore regular sports activities so that it has an impact on the low level of physical fitness. This study aims to test the effectiveness of using a fitness training product in the form of a “BBC Exercise” model for maintenance of physical fitness. This research was conducted at STKIP Citra Bakti Ngada, involving 15 students with an age range ≤19 years as research subjects. The research design used was a pre-experimental time series with a one group pretest-posttest design. Data were collected by measuring physical fitness using the TKJI format (Indonesian Physical Fitness Test). The results of the pretest-posttest difference test obtained the sig value. (2-tailed) paired samples t-test (0.000) is smaller than (0.05) or (p <0.05). This means that there is a significant effect of using the